Prevalence of Gastrointestinal Nematodes in Silvery Mole-Rats in Morogoro Region, Tanzania - Debora Elias Shija; Jahashi S. Nzalawahe; Mungo Kisinza Ngalameno; Eliakunda M. Mafie (Journal of Applied Veterinary Science And Technology, 2025)
Background: Exploring the nematode diversity in silvery mole rats opens up a fascinating avenue for understanding the intricate relationships between underground-dwelling mammals and their parasites. It is intriguing to consider the potential transmission of parasitic zoonotic between humans, livestock, and silvery mole rats due to the notable interactions of these animals. Purpose:  This study aims to acquire crucial information about the nematode fauna in silvery mole rats in the Morogoro region, Tanzania. Method: A survey of nematode parasites in silvery mole rats was conducted in the Morogoro region, from March to June 2023. Collected rats were euthanized using Diethyl Ether, and dissected to remove the gastrointestinal tract (GIT). Adult worms were collected and preserved in 70% ethanol. A flotation method and lactophenol mounting techniques were employed to process gastrointestinal contents and adult roundworms. The prevalence of nematodes was computed, and a chi-square test was applied to assess the relationship, a p-value< 0.05 was considered significant. Results: The examination of the gastrointestinal tract contents revealed two nematode taxa; Physaloptera spp and Strongyloides spp. The overall prevalence of nematode infection was 38.69% (53/137), with Physaloptera species being the most prevalent (37.22%). Adult rats had a lower infection risk than sub-adult rats. Female silvery mole rats were at higher risk of being infected compared to males. Conclusion: The study established two nematodes in silvery mole rats of Morogoro region, Tanzania, which are Physaloptera spp and Strongyloides spp.